Lippia gracilis e seus compostos majoritários: efeitos na sobrevivência, biologia e comportamento de Euschistus heros - Tavares, Swamy Rocha Siqueira Abreu (2023)
Euschitus heros (Hemiptera: Pentatomidade) is one of the most prominent phytophagous insects found in soybean areas. Its importance lies in the direct damage it causes to the plant pods, reducing seed viability, grain quality, and oil yield. The brown stink bug also leads to a physiological imbalance known as “crazy soybean”, which hinders grain harvest. The primary control method has been the use of synthetic insecticides, including neonicotinoids such as imidacloprid. Although this molecule is widely used for stink bug management, control failures in soybean growing areas have been reported, likely due to issues related to resistance. To discover new insecticidal molecules, the present study evaluated the effects of sublethal doses of essential oils from Lippia gracilis accessions, of the major compounds of Lippia gracilis – thymol and carvacrol, and of the commercial insecticide imidacloprid on the survival and on the biological, demographic, and behavioral parameters of the brown stink bug in soybean. In the first chapter, we evaluated the effect of a sublethal concentration of the essential oils of the L. gracillis chemotypes thymol and carvacrol, of their respective major compounds, and of imidacloprid on the development, reproduction, and demographic parameters of the insect. Among the treatments assessed, the major compound thymol and the commercial insecticide were most toxic to third-instar nymphs. Additionally, this major compound significantly reduced the nymphal stage, the number of nymphs, and egg viability, whereas the synthetic insecticide maintained the same viability as the control. Furthermore, thymol affected the life table parameters of the insect, reducing the intrinsic growth rate and the finite rate of increase, as well as extending the doubling time and average generation time. In the second chapter, we evaluated the effects of the treatments on behavior. In general, the essential oils and the major compounds caused irritability in nymphs and adults. Furthermore, changes in behavior patterns were observed; thymol reduced the average speed and distance traveled, while increasing angular speed and meandering behavior. The insecticide effects were similar to those of the control. In nymphs, all the oils and the major compounds increased the frequency of cleaning. For adults, only essential oils interfered with this process.